Social aspect in the novel Dikta dan Hukum by Dhia’an Farah - Suroto, Avifah Nur Rizky; Haris Supratno (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to reveal the text that contains the aesthetic value of coffeein the novel The Coffee Memory by Riawani Elyta using Ronald Tobin’s gastronomicapproach. The method used in this study is a qualitative analysis involving theresercher’s reading, recording, and interpretation of the text in the novel. The datacollection technique involved carrying out reading and note-taking activities, whichwould then be analyzed by identifying and interpreting data and linking the datafindings with gastronomic theory. This study obtained the results that the image ofcoffee can relate to the experiences experienced by humans. Not only that, but coffeealso has aesthetic value, starting from its name, art, and the history of these uniquecoffees. Through that, culinary can have differences from other culinary delights,ultimately making it a person's identity.